Sociodemographic and Lifestyle Factors as the Risk of Diabetic Foot Ulver in the University of Malaya Medical Centre - Misliza, A.; Said, Mas Ayu (Faculty of Medicine, University of Malaya, 2009)
A case-control study was conducted between November 2005 and May 2007 in the University of Malaya Medical Centre (UMMC), University of Malaya, Kuala Lumpur, Malaysia. The objective of this study was to identify specific socio-demographic and lifestyle factors which were associated with foot ulcer in Type 1 and Type 2 diabetes patients. There were 125 cases and 250 controls by using universal sampling. Diabetic foot ulcer was defined as “the full thickness skin break at least to Grade 1 Wagner Stage, occurring distal to malleoli”. The case was defined as the diabetic patient who was newly diagnosed or who has a known case of diabetic foot ulcer and the control was defined as the diabetic patient without active foot ulcer. Data was collected via face-to-face interview using a structured questionnaire. Results showed that diabetic patients at younger age group, 44 years old and less (OR 5.90 95% CI 2.31, 15.10), Indian (OR 3.24 95% CI 1.66, 6.30), and smoker (OR 3.85 95% CI 1.77, 8.35) were the independent risk factor for diabetic foot ulcer. (JUMMEC 2009; 12 (1): 15-21)